EXPLORING IMPLEMENTATION OF STUDENTâ€™S DIARY AS A LEARNING REFLECTION IN EFL WRITING SKILL - Wahyuni, Irma (Study Program of English Literature, 2019)
This paper is a qualitaive case study regarding one of learning strategies in English as Foreign Language (EFL) writing, literally called â€œstudentâ€™s diaryâ€. The studentsâ€™ diary can be defined as a brief narrative text created by students that might be a brief summary of what they have learnt, teachersâ€™ feedback and evaluation, or even a general impression about their writing process. It aims to naturally encourage students to conduct a comprehensive reflection on their progress in EFL writing through â€œa diaryâ€ in each writing class they have. As what has been perceived among EFL scholars, the use of studentâ€™s diary is effective in enhanching studentâ€™s interest in writing and it can improve studentsâ€™ writing as well. The participants of this study are 30 students of EFL classroom in the fourth semester at STKIP Muhammadiyah Bogor who have taken the various writing subjects in their previous semesters. The researcher tried to investigate how the typical of studentâ€™s diary for learning reflection is, how the real implementation of studentâ€™s diary is conducted in EFL learnersâ€™ learning process, and to what extent it can be effective related to the strengths and weaknesses involved in the implementation process. Advisory and suggestion on giving corrective feedback regarding linguistic aspects in studentsâ€™ writing in the use of studentâ€™s diary as well is presented as the implication of this research for further related studies